COMPENSATORY CYCLICAL BANK ASSET ADJUSTMENTS: REPLY - Luckett, Dudley G. (Journal of Finance, 1962)
Gray first takes me to task for having misapplied Warren Smith's analysis dealing with the wider spread needed to recoup capital losses when a bank switches securities at depressed prices.33 Warren L. M. Smith, “On the Effectiveness of Monetary Policy,” American Economic Review, XLVI (September, 1956),590–93. Gray correctly observes that, in applying Smith's analysis to the spread between Treasury bonds and customer loans, I have implicitly carried over Smith's assumptions that the two securities are of identical maturity. While this assumption is unobjectionable in the Smith context, it is clearly out of place in my own. Gray's point is well taken. Nevertheless, I wonder if the error is quite so glaring as Gray seems to feel. In the first place, the increased loan demand is likely to be considerably more permanent than any particular loan. Thus, while the bank may be making only a 3-month loan, it will generally expect to be able to relend the funds to another customer when the 3 months are up. Moreover, Silverberg's analysis indicates that the typical response of banks to an increased loan demand is to sell off their intermediate-term bonds (1–5 years) and allow their longer-term bonds (over 5 years) to become intermediate-term through the passage-of-time effect. Given these two conditions, the difference in maturity may not be so important as would at first appear.44 Gray takes a step in his analysis at this point which I find puzzling. On p. 647 he says: “Furthermore, the costs of administering a loan exceed those of investment supervision, so that any differential in gross yield should be enhanced by any cost difference, as well as by any requisite risk premium.” But, since the raison d'être for the spread is risk and administrative costs, I fail to see why the differential should increase when a bank increases its loans. As an alternate explanation of the shortening of the security portfolios of commercial banks, Gray suggests that this may have been a secular adjustment occasioned by the reintroduction of flexible monetary policy in 1951. If I understand him correctly, Gray would argue that the shortening would have occurred even in the absence of an expanded loan demand because the “reintroduction of considerable flexibility in bond prices, coupled with a secular increase in yields may well have shortened the optimum maturity of the portfolio” (p. 648). Gray himself raises the major objection to this interpretation of the data: Why should a secular adjustment occur in a cyclical fashion? His explanation is that banks took their capital losses in times of high net current earnings in order to be able to “show quite adequate profit figures to their stockholders and to the public.” While I cannot, of course, disprove this theory, it does seem to me to be stretching things to assert that banks have deliberately engaged in maximizing their capital losses for purposes of window dressing. Moreover, even if one were to accept this explanation, it still does not account for the cyclical upswings in the long-term bond holdings of banks; we are still left with the question of why, if banks were engaged in the strictly secular action of reducing their portfolio of long-term governments, they should have acquired nearly $15 billion worth in 1953 and over $7 billion worth in 1958. In my paper I left it an open question whether the banking system had disposed of its long-term governments through open-market sales or through the passage-of-time effect.77 Op. cit., p. 58, n. 12. Silverberg's comment closes this gap and, in so doing, makes a significant contribution to the discussion.